Javanese Nomads’ Language Attitude Towards Javanese and Batak Toba Languages - Manik, Kresna Ningsih; Nasution, Lonni Nur Iffah; Purba, Nancy Angelia; Tarigan, Merry Susanty Br (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study investigates the language attitude of Javanese Nomads’ towards Javanese and Batak Toba Language in Sumbul City. The participants of this study are the age of 17 to 60 years. There are four informants ranging in age from 17 to 25, there are four informants of ethnic married partner, and four informants ranging in age from 40 to 50 years old and have been living in Sumbul city for more than 10 years. The study id based on the purposive sampling technique. Technic for data collection is supported by interview transcript and some other instruments such as field note, recording tools. Data from questionnaire is analyzed by using the steps: (1) reduction the data into positive and negative attitude, (2) data display through textual representation on Javanese and Tobanese language attitude, (3) verification and drawing conclusion. The data from interview is analyzed by (1) transcribing the data from tape recorder, (2) classifying data into some categories of factors contribute to positive or negative attitude, (3) verifying the data through asking interview participant to do confirmation and (4) come to conclusion. Cognitive Factors shows that Javanese inhabitants’ comprehension to their language is proficient enough since more than 50 % of informants realize that their language is their typical characteristic of their ethnic, however 25 % of the informants who are dominated by young generation rarely use their ethnic language. As many as 25% of used Indonesian and Toba Batak language to communicate in daily life interaction, this is caused by work factors as they have to adapt environment dominated by other ethnic and Indonesian language as official language in their work institution. Affective Aspects of Javanese inhabitants aged 17 – 25 most frequently use Indonesian language at school and campus than Javanese language. Conative Factors shows Javanese informants (60%) rarely or even never use Javanese language as they seldom interact or meet up with Javanese people even they meet up with Javanese people they prefer to use Indonesian language. However, four informants (40%) sometimes still use Javanese language to communicate at home, big family gathering, interact with other Javanese people those who have eagerness to keep using Javanese language in communication in market, workplace, mosque. Migrating is caused by some factors is one causative factor to the language shift and even language lost